2018
DOI: 10.1007/s10639-018-9844-x
|View full text |Cite
|
Sign up to set email alerts
|

Digital writing tools from the student perspective

Abstract: Along with digital development, new possibilities for communicating have emerged. The younger generation has adopted these new possibilities to a great extent. In order to be able to utilise the opportunities offered by digital tools when writing, access to digital tools is essential. Schools need to develop a writing education that meets students' contemporary writing needs. In considering this, it is important to learn more about the gains and the losses in digital writing. The purpose of this study was to u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 25 publications
(44 reference statements)
0
8
0
3
Order By: Relevance
“…Based on the four skills of the English language, writing gives the impression to be the most difficult part to learn. Writing as Dahlström (2018) mentions "….is important because it's used extensively in higher education and in the workplace. If students don't know how to express themselves in writing, they won't be able to communicate well with professors, employers, peers, or just about anyone else" (p. 3).…”
Section: Theorical Frameworkmentioning
confidence: 99%
“…Based on the four skills of the English language, writing gives the impression to be the most difficult part to learn. Writing as Dahlström (2018) mentions "….is important because it's used extensively in higher education and in the workplace. If students don't know how to express themselves in writing, they won't be able to communicate well with professors, employers, peers, or just about anyone else" (p. 3).…”
Section: Theorical Frameworkmentioning
confidence: 99%
“…The further benefit of digital writing platforms and tools is to make students more autonomous in learning. Dahlström (2019) divided the perspectives of digital writing tools affordance into four, Write-ability, edit-ability, story-telling ability, and accessibility. From those four divisions, it is revealed that the students can be more independent in developing their writing styles, interactions, stories, languages, focuses, and ideas in writing.…”
Section: Digital Writing Platformsmentioning
confidence: 99%
“…Kegiatan ini dilakukan pendidik di perpustakaan sekolah yang menyediakan berbagai akses literasi cetak maupun digital dalam pelajaran bahasa Inggris dan bahasa Indonesia melalui tugas-tugas menulis uraian suatu topik. Dahlstrom (2019) dalam penelitiannya yang berjudul Digital Writing Tools from Student Perspective menyatakan bahwa keberhasilan peserta didik dalam menulis di media digital sangat bergantung pada akses digital, kesempatan untuk terus berlatih dan pengalaman menulis di media digital. Konsep affordance atau aksi peserta didik ditekankan untuk lebih sering kontak dengan apa yang dikerjakan, dalam hal ini kegiatan digital writing.…”
Section: Optimasi Kompetensi Menulis Siswa DI Media Digitalunclassified